Forest governance at the local level: a study on social forestry institution in Dhaka forest division, Bangladesh - Chowdhury, Ruhul Mahiman (Masters of Development studies, BRAC University, 2010)
This thesis is submitted in a partial fulfillment of the requirement for the degree of Masters of Development studies.